Food consumption in Brazil: influence of beef on environmental impact and nutritional quality of the diet - Josefa Maria Fellegger Garzillo; Vanessa Fadanelli Schoenardie Poli; Fernanda Helena Marrocos Leite; Euridice Martinez-Steele; Priscila Pereira Machado; Maria Laura da Costa Louzada; Renata Bertazzi Levy; Carlos Augusto Monteiro (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To estimate beef consumption and its influence on carbon and water footprints, as well as to improve the nutritional quality of the Brazilian diet. METHODS The amount of beef and other foods consumed was evaluated by two 24-hour food records in a representative sample of the Brazilian population ≥ 10 years of age (n = 32,853) from 2008 to 2009. The environmental impact of the diet considered the coefficients of the carbon footprint (gCO2 and/kg) and the water footprint (liters/kg) of the foods, as well as their nutritional quality considering the nutrient composition of each food associated with the prevention of nutritional deficiencies or the increase/decrease in chronic disease risk. Linear and logistic regression models, crude and adjusted for sex, age, education, income, region, and area, were used to respectively study the association of fifths of the caloric contribution of beef with the environmental impacts of the diet and inadequate nutrient intake. RESULTS Carbon and water footprints and protein, iron, zinc, vitamin B12, saturated fat, and sodium contents were higher in the fraction of the diet composed of beef, whereas fiber and added sugar contents were higher in the fraction composed by the other foods. Dietary beef contribution was directly associated with the carbon and water footprints of the diet and the risk of saturated fat and sodium excess, besides fiber insufficiency, inversely associated with the risk of protein, iron, zinc, and vitamin B12 insufficiency. CONCLUSION Reducing beef consumption in Brazil would also reduce the carbon and water footprints of the diet, as well as the risk of chronic diseases related to food. Therefore, in order not to increase the risk of nutritional deficiencies, monitoring the increased intake of other foods rich in protein, iron, zinc, and vitamin B12 is suggested.